Protective Effect of Carnobacterium spp. against Listeria monocytogenes during Host Cell Invasion Using In vitro HT29 Model - Pilchová, Tereza; Pilet, Marie-France; Cappelier, Jean-Michel; Pazlarová, Jarmila; Tresse, Odile (Frontiers in Cellular and Infection Microbiology, 2016)
The pathogenesis of listeriosis results mainly from the ability of Listeria monocytogenes to attach, invade, replicate and survive within various cell types in mammalian tissues. In this work, the effect of two bacteriocin-producing Carnobacterium (C. divergens V41 and C. maltaromaticum V1) and three non-bacteriocinogenic strains: (C. divergens V41C9, C. divergens 2763 and C. maltaromaticum 2762) was investigated on the reduction of L. monocytogenes Scott A plaque-forming during human infection using the HT-29 in vitro model. All Carnobacteria tested resulted in a reduction in the epithelial cell invasion caused by L. monocytogenes Scott A. To understand better the mechanism underlying the level of L. monocytogenes infection inhibition by Carnobacteria, infection assays from various pretreatments of Carnobacteria were assessed. The results revealed the influence of bacteriocin production combined with a passive mechanism of mammalian cell monolayers protection by Carnobacteria. These initial results showing a reduction in L. monocytogenes virulence on epithelial cells by Carnobacteria would be worthwhile analyzing further as a promising probiotic tool for human health.